FEMINISM AND INDONESIAN WOMEN'S FREEDOM IN PHILOSOPHY - Lulu Andriani Sulasti; Dewi Robiatun Muharomah; Gustini Wulandari; Yoga Mahendra (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
Feminism as a social movement and thought has fought for gender equality and women's freedom in various parts of the world. In Indonesia, the feminist movement emerged as a response to the dominant patriarchal social structure and culture that limits women's roles in society. This article aims to examine the role of feminism in fighting for women's freedom in Indonesia through a philosophical study. Using the literature review method, this article explores the views of Indonesian and international feminist thinkers on women's freedom and how the philosophy of feminism is applied in the context of Indonesian culture. Based on this analysis, Indonesian feminism can be understood not only as a social movement, but also as a philosophical foundation that changes the understanding of the role and rights of women in Indonesian society.